Multiobjective Programming Strategy of Small- and Medium-Sized Microenterprise Credit Based on Random Factors - Zhuoran Fan; Jilong Xu; Yuchen Li (Journal of Function Spaces)
In this paper, we select eight indicators from the aspects of an enterprise’s bill transaction information, namely, whether the enterprise’s loan is in breach of contract, effective invoice rate, total utilization rate of price and tax, negative invoice rate, strength of enterprise, coefficient of variation, flow efficiency of assets, and influence of upstream and downstream enterprises; then, we construct an evaluation index system. According to different industries, different categories, and the impact of random factors, we divide the types of enterprises into 10 categories. Then, we use three kinds of Poisson random numbers to carry out numerical simulation on the total price and tax of enterprises in different industries under the influence of COVID-19.